Engineering geology: development and perspectives - ΚΟΥΚΗΣ, Γ. (Bulletin of the Geological Society of Greece, 2002)
This paper refers to the following issues: the definition of Engineering Geology, diachronic development, professional practice and registration, teaching and training, responsibilities - limitations - future